ECHOCARDIOGRAPHIC ANALYSIS OF LEFT ATRIAL DEFORMATION USING THE SPECKLE TRACKING METHOD IN PREDICTING THE COURSE OF ATRIAL FIBRILLATION - Кожин, Михайло; Ходош, Едуард; Ринчак, Петро (SWorldJournal, 2025)
This study examines the diagnostic value of echocardiographic parameters of left atrial cardiomyopathy in paroxysmal atrial fibrillation. 80 subjects with atrial fibrillation were examined using echocardiography with strain analysis over 24-month follow-